PWE-075 Day-1 post-operative alt does not predict morbidity following liver resection – analysis of a contemporary cohort of 110 patients. (22nd June 2015) - Nair, A; Papis, D; Bhogal, RH; Prasad, A; Kaur, A; Khan, S; Lam, FT; Marangoni, G
Abstract : Introduction: Predicting the risk of post-operative complications following liver resection is an integral part of liver surgery planning. Post-operative liver function tests have been used for prediction of liver failure. We sought to clarify whether post-operative day 1 (POD-1) Alanine aminotransferase (ALT) was predictive of complications in a contemporary cohort of liver resections. Method: Interrogation of a prospectively maintained database from January 2013 to December 2014 was performed. POD-1 ALT was analysed against the occurrence of post-operative complications which were graded as per the Clavien-Dindo classification. Results: There were 114 liver resections; 4 patients were excluded as they underwent synchronous pancreas/liver surgery. There were 61 males (56%) and median patient age was 65 years. Sixty-nine (63%) resections were performed for colorectal liver metastases. Forty-two patients (38%) received neoadjuvant chemotherapy. There were 58 (52%) non-anatomical resections and 29 (26%) major hepatectomies. Forty-three (39%) patients had > 3 segments resected. The Pringle manoeuvre was used in 55 patients (50%) for a median (IQR) time of 18 (10–25) minutes. Intra-operative radiofrequency ablation (RFA) was employed as an adjunct to resection in 17 (16%) patients. Overall morbidity was 28% (n = 31) whereas mortality was 0.9% (n = 1). There were 16 Grade 2 (15%), 14 Grade 3 (13%) and no Grade 4 complications. Mean POD-1 ALT (IU/L) was significantly higher in the group of patients who underwent RFA (674 vs 330; p < 0.0001). POD-1 ALT was not statistically higher in the Pringle group (411 vs 353; p = 0.189). No significant increase in mean POD-1 ALT was seen in patients who had >grade 2 Clavien-Dindo complications (450 vs 357; p = 0.585). Conclusion: Our data shows that POD-1 ALT does not reliably predict the occurrence of post-operative complications after liver resection. Disclosure of interest: None Declared.